2021
DOI: 10.3390/ma14092143
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Computational Model for Damage Behavior of Metal-Matrix Composites Emphasizing the Effect of Particle Size and Volume Fraction

Abstract: In this paper, an integrated numerical model is proposed to investigate the effects of particulate size and volume fraction on the deformation, damage, and failure behaviors of particulate-reinforced metal matrix composites (PRMMCs). In the framework of a random microstructure-based finite element modelling, the plastic deformation and ductile cracking of the matrix are, respectively, modelled using Johnson–Cook constitutive relation and Johnson–Cook ductile fracture model. The matrix-particle interface decohe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…However, as indicated in Table 1, the height of each layer after polishing was 1-2 µm. If we use P = 0.063 (µm/pixels), the lateral surface of the crystal will be expressed as shallow needle-like squares, and the surface lacks uniformity, due to the small value of P. In order to reproduce the result well, we defined P as expressed in Equation (15), with P = P × r and r = 30 ∼ 60.…”
Section: Nodes and Stackingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as indicated in Table 1, the height of each layer after polishing was 1-2 µm. If we use P = 0.063 (µm/pixels), the lateral surface of the crystal will be expressed as shallow needle-like squares, and the surface lacks uniformity, due to the small value of P. In order to reproduce the result well, we defined P as expressed in Equation (15), with P = P × r and r = 30 ∼ 60.…”
Section: Nodes and Stackingmentioning
confidence: 99%
“…Meanwhile, according to conventional studies, the size and shape of the microstructure affect the strength, toughness, and creep resistance of the structure [9][10][11]. However, it is not easy to reflect and demonstrate this with the finite element method [12][13][14][15]. This is because the factor used in the finite element method is the shape of the structure and does not include the microstructure of the structure itself.…”
Section: Introductionmentioning
confidence: 99%
“…In [ 13 ], the method was used to show that the effective mechanical properties of an Al–B 4 C composite can be influenced by residual stress fields created during the fabrication by stir casting. Most computational studies reported in the literature assume that a perfect bond exists between particles and matrix [ 12 , 13 , 14 , 15 , 16 , 17 ]. Some studies modeled the bond strength by directly using cohesive-zone (CZ) approaches to investigate particle-matrix debonding, which initiates prior to the final failure of the material [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies modeled the bond strength by directly using cohesive-zone (CZ) approaches to investigate particle-matrix debonding, which initiates prior to the final failure of the material [ 15 ]. Nevertheless, it is commonly assumed that particle-matrix debonding only occurs after global effective yielding initiates [ 17 ]. The exact effect of very weak or nonexistent particle-matrix bonding strength on the effective elastic mechanical properties of AMCs is still not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…These techniques are relatively cost-effective and could be applied in numerical and experimental approaches for modeling or simulating MMCs' manufacturing and machining [22]. A numerical model for analyzing the effects of PMMCs particulate size on damage mechanisms was developed by S. Gad et al [23]. This paper's computational finite element (FE) model was proposed to determine the elastoplastic behavior of A359/SiC particulate composite.…”
Section: Introductionmentioning
confidence: 99%